Rationality of Prescription of Antibiotics in Patients with Acute Upper Respiratory Tract Infection - Hertina Silaban; Welita Selyn Dami; Erica Gilda Misnawati Simanjuntak; Daniel Reinaldo Parsaoran Situmorang; Jimmi M. P. Aritonang (Indonesian Journal of Global Health Research, 2025)
Acute upper respiratory tract infection is an infectious disease caused by microorganisms, one of which is bacteria, so antibiotics are given. Rational use of antibiotics can provide benefits for recovery and does not cause harm that can cause problems or threats to the health of sufferers. Inappropriate administration of antibiotics can hurt patients, one of which is antibiotic resistance. Objective to obtain an overview of the rationality of antibiotic prescription in patients with acute upper respiratory tract infections at the Baun Health Center, Kupang Regency in 2020. This study was conducted using non-experimental research that is descriptive by taking medical record data retrospectively. Sampling was carried out using the non-probability sampling technique and the purposive sampling type, namely determining the sample based on certain considerations where the sample must meet the inclusion criteria, the number of cases of acute upper respiratory tract infections in 2020 was 226 cases. Data collection using secondary data, namely data obtained from medical records of patients with acute upper respiratory tract infections in 2020 at the Baun Health Center, Kupang Regency. The data obtained will be analyzed descriptively quantitatively, including: the percentage of rational and irrational antibiotic prescriptions, the frequency of types of antibiotics used. Acute upper respiratory tract infections (URTIs) in Baun Health Center mostly occurred in the 20–44 years age group (32.7%) and were more often experienced by women (59.3%), with the most common diagnosis being rhinosinusitis (48.2%); The most commonly used antibiotic was amoxicillin monotherapy, given to 89.4% of patients; The use of antibiotics showed 100% accuracy of indication and patient, 90.3% accuracy of drug, 65% accuracy of dose, and 55.3% rationality of use. Most in the 20–44 years age group (28.3%) and women (39.3%). Acute upper respiratory tract infections (URTIs) at the Baun Health Center, Kupang Regency, occurred most in the 20–44 years age group and were more often experienced by women, with rhinosinusitis as the most common diagnosis. Antibiotic use was dominated by amoxicillin monotherapy. Evaluation of the appropriateness of antibiotic use showed quite good results in terms of indications, patient selection, and type of drug, but there were still shortcomings in the appropriateness of dosage and overall rationality of use. The rationality of treatment was most often found in the 20–44 years age group and in female patients.